A comprehensive prognostic and immunological implications of Gremlin 1 in lung adenocarcinoma - Li, Hongyan; Zhou, Yang; Xiao, Jiaqing; Liu, Fang (Frontiers in Immunology, 2025)
BackgroundLung adenocarcinoma (LUAD) is a prevalent form of lung cancer globally, known for its high invasiveness, metastatic potential, and notable heterogeneity, particularly in its response to immunotherapy. Gremlin 1 (GREM1) is implicated in tumor progression and poor prognosis in multiple cancers. However, GREM1’s specific role in LUAD remains unclear. This study systematically examines GREM1 expression in LUAD and its association with tumor progression, immune microenvironment, and prognosis.MethodsGene expression data from the TCGA and GSE31210 databases were analyzed using Weighted Gene Co-expression Network Analysis (WGCNA), GO and KEGG enrichment analyses. The prognostic value of GREM1 was evaluated through survival analysis, Cox regression, and Kaplan-Meier curves. Additionally, immune microenvironment analysis was conducted to explore the relationship between GREM1 and immune cell infiltration. In vitro experiments, including Western blot and assays for cell proliferation, migration, and invasion, were performed to confirm the specific role of GREM1 in LUAD cells.ResultsGREM1 was significantly upregulated in tumor tissues and correlated with poor prognosis. Moreover, GREM1 was significantly associated with immune cell infiltration and immunotherapy response within the immune microenvironment. In vitro experiments confirmed that GREM1 overexpression significantly promoted LUAD cell proliferation, migration, and epithelial-mesenchymal transition (EMT), whereas GREM1 knockdown suppressed these functions.ConclusionsA comprehensive analysis indicates that GREM1 is crucial in LUAD progression, with its overexpression predicting poor prognosis. GREM1 could be a potential therapeutic target for LUAD, providing insights for personalized therapy optimization.